Enhancing the Teaching-Learning Process through Neutrosophic Statistical Analysis of Professional Competencies and Metacognitive Strategies - Dante Manuel Macazana Fernandez; Wilder Fabio Ramos Palacios; Daniel Amílcar Pinto Pagaza; Mary Liz Mendoza Hidalgo; Tula Margarita Espinoza Moreno; Mayra Susan Albán Taipe (Neutrosophic Sets and Systems)
In the educational field, teaching effectiveness depends on the interaction between professional competencies and teachers' metacognitive strategies. Therefore, the present study has proposed to evaluate the relationship between professional competencies and metacognitive strategies, by using the management of indeterminacies to improve the teaching-learning process. To this end, the neutrosophic statistics method was applied to analyze data on meta-cognitive competencies and strategies in a group of teachers. Among the results, a general positive relationship was revealed between professional competencies and metacognitive strategies, with significant variations in specific areas. Finally, it has been concluded that there is a significant connection, where the variability suggests the need to strengthen training in specific competencies and metacognitive strategies to optimize the educational process.